Estimasi Potensi Panas Bumi Sebagai Supply Daya (Perencanaan Reaktivasi Jalur Kereta Api Madiun Slahung Ponorogo - Sunardi, Sunardi; Wirawan, Willy Artha; Aghastya, Adya (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2018)
This study aims to measure the reserve of geothermal energy for the use of alternative energy as a supply of reactive power planning for the Madiun-Ponorogo railway line. This research is a type of exploratory research that is qualitative and descriptive. The results showed that geothermal power is usually expressed as power in the electric capacity of the extraction period for a projection of 30 years. Power is calculated to reach 1900,04074 GWe, and the power is extracted by 50% percent to 950,0203700545 GWe as recoverable energy. After the recovery factor is obtained, the power output in the form of electricity is 228,0048888 GW so that it has the potential as an alternative energy supply.